PERBANDINGAN HASIL PEWARNAAN PREPARAT HISTOLOGI MENGGUNAKAN XYLOL DAN MINYAK JAGUNG YANG DIPANASKAN PADA PROSES DEPARAFINISASI - Mufidah, Zahra; Wiryanti, Wiwin; Durachim, Adang; Rahmat, Mamat (Jurnal Kesehatan Siliwangi, 2024)
Deparaffinization removes residual paraffin from tissue, enabling optimal dye absorption in histological preparations. While xylol is commonly used, its high exposure risks necessitate exploring safer alternatives. The research compares the efficacy of corn oil 60°C to xylol as a deparaffinization agent. Heated corn oil is necessary to reduce viscosity and increase solubility. Corn oil can also be used as an environmentally friendly and cost-effective alternative. The research employed a descriptive approach, comparing staining results of kidney tissue preparations from control and experimental groups. Assessment criteria included color uniformity and contrast, determined by the difference in Optical Density values between nuclear and cytoplasmic staining. Due to non-normal data distribution and the comparison of two unpaired means, the Mann-Whitney U test was utilized for statistical analysis. The results obtained an Asymp sig value of 0.002 where the value is included <0.05 which explains that there is a significant different on the staining results of tissue preparations deparaffinized using xylol and corn oil 60°C with the percentage of staining results in the good category deparaffinized using corn oil only reached 26.67%. The results showed that there were differences in the staining results of kidney tissue preparations deparaffinized using xylol and 60°C corn oil so that 60°C corn oil has less effective to be an alternative deparaffinization agent to replace xylol.